Sosialisasi Dampak Globalisasi Di Era Digital Terhadap Kualitas Pembelajaran Bagi Siswa Di MIN 1 Langkat - Tuti Rezeki Awaliyah Siregar; Fahrunnisa Fahrunnisa; Muhammad Sulaiman (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The aim of this activity is to (1) determine the impact of globalization of education on the quality of learning in class V of MIN 1 Langkat (2) determine the efforts and strategic steps towards the quality of learning in class V A of MIN 1 Langkat in the era of digital globalization. The results of this research are: 1) The impact of globalization in the digital era on the quality of learning in class V A of MIN 1 Langkat consists of two impacts, namely positive impacts and negative impacts. Positive impacts include globalization providing opportunities for educators and students to learn science and technology as a learning reference. Meanwhile, negative impacts include teachers not yet 100% implementing digital-based learning in schools because the availability of learning technology in schools is still incomplete. Several efforts that can be made and strategic steps in learning are divided into three activities with several stages, namely (a) Preliminary activities in the form of a phase of getting used to class order, motivation and advice. (b) Core activities include four stages, namely the understanding or reasoning stage, the application stage and the meaning stage. (c) The closing activity is evaluation and reflection between students and teachers regarding the implementation of learning in class V A of MIN 1 Langkat Tanjung Pura.Abstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formula.